Operation of diesel engine with fuels treated with nanoparticle additives. Issue 1 (December 2020) - Ivanov, Zdravko; Mihaylov, Veselin; Sitnik, Lech; Sroka, Zbigniew
Abstract: Treatment of materials with nano-sized elements is widely used in the automotive industry. This application is associated both with surface treatment of parts and in the form of various mixtures. The use of nanoparticles as an additive to oils and fuels aims to impact the energy efficiency of the engine in order to improve mechanical losses and its environmental performance. Improving mechanical losses leads to a reduction in energy consumption and hence to a reduction in carbon emissions. Published research in this regard has shown an impact on various physical processes related to engine performance. In this paper are shown the results from performed studies on a direct injected diesel engine when working with oil and fuel additives, based on carbon nanoparticles. The results show an improvement in the operation of the fuel injection system and reduction in the mechanical losses in the engine.